2017
DOI: 10.18632/oncotarget.18811
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib improves lipiodol deposition in transarterial chemoembolization of Chinese patients with hepatocellular carcinoma: a long-term, retrospective study

Abstract: ObjectiveThough synergy of sorafenib and transarterial chemoembolization (TACE) in hepatocellular carcinoma (HCC) is well discussed in previous reports, association of lipiodol retention by sorafenib addition to TACE with the survival outcomes remain elusive. Therefore, we studied the impact of sorafenib addition to TACE on survival outcomes mediated by lipiodol retention.Materials and MethodsThis is a long-term, retrospective, single-center study using medical records of patients diagnosed with HCC at the Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…A prospective clinical study has identified that TACE treatment may result in increased serum vascular endothelial growth factor levels one to two days following the procedure, which could increase the chance of extrahepatic spread and unfavorable outcomes [25,26]. Previous studies have also suggested that sorafenib treatment may improve lipiodol retention in HCC [19]. The latter provides support of better local control of aHCC, which may improve the survival, even in a patient with extrahepatic metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective clinical study has identified that TACE treatment may result in increased serum vascular endothelial growth factor levels one to two days following the procedure, which could increase the chance of extrahepatic spread and unfavorable outcomes [25,26]. Previous studies have also suggested that sorafenib treatment may improve lipiodol retention in HCC [19]. The latter provides support of better local control of aHCC, which may improve the survival, even in a patient with extrahepatic metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for incorporating TACE during sorafenib treatment results from the clinical observation that lipiodol deposition is significantly increased when sorafenib is added after TACE [19]. Certain local tumors can be controlled with TACE, thus preventing local disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that lipiodol deposition in HCC tumour might be used as an imaging indicator to evaluate TACE therapeutic efficacy [21][22][23][24]. By identifying the lipiodol deposition patterns on post-TACE CT, we first calculated the proportion of lipiodol deposition in all enrolled patients and categorized them into two different groups with 50% as cut-off according to previous reports [25][26][27] (Fig. 5A).…”
Section: Correlation Between Lipiodol Deposition and Cnvs In Pre-tace...mentioning
confidence: 99%
“…In theory, the combination of TACE and anti angiogenesis drugs is effective and feasible. The theory of potential synergistic effect of targeted drugs combined with TACE is still developing, especially at the molecular level [23,24,25,26,27]. Child Pugh grades were different (P=0.038).…”
Section: Discussionmentioning
confidence: 99%